2018
DOI: 10.1021/acsearthspacechem.7b00150
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Plant-Available Mg, Ca, and K Pools in the Soil—An Isotopic Dilution Assay

Abstract: In many forest ecosystems, plant-available pools of Mg, Ca, and K are assumed to be stored in the soil as exchangeable cations adsorbed on the cation exchange complex (exchangeable pools). However, between soil minerals and exchangeable cations exists a gradient of Mg, Ca, and K storage forms that have not been fully characterized and may play an important role in plant nutrition and biogeochemical cycles. We hypothesize that sources of Mg, Ca, and K in the soil other than the conventionally measured exchangea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 82 publications
4
10
0
Order By: Relevance
“…The majority of samples showed an E X :Exch X ratio greater than 1 for Ca, Mg and K. For a substantial proportion of the dataset (43%, 27% and 47% respectively for Ca, Mg and K), E x pools were more than 50% larger than the Exch X pools. This trend was confirmed by a Wilcoxon-Mann-Whitney comparison test that showed that isotopically exchangeable pools were significantly larger than their respective exchangeable pool, though homoscedasticity between the compared pools was not met for Mg. Our results are consistent with previous studies for Ca and K. Blum and Smith 41 showed, in an isotopic dilution assay using the 45 Ca radiogenic isotope over 16 different type of soils, that E Ca was significantly greater than Exch Ca for 6 soil samples, lower for 2 samples and not significantly different for 8 samples. Reeve et al 43 showed that 5 soil samples out of 7 showed an E Ca pool greater than the Exch Ca pool.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The majority of samples showed an E X :Exch X ratio greater than 1 for Ca, Mg and K. For a substantial proportion of the dataset (43%, 27% and 47% respectively for Ca, Mg and K), E x pools were more than 50% larger than the Exch X pools. This trend was confirmed by a Wilcoxon-Mann-Whitney comparison test that showed that isotopically exchangeable pools were significantly larger than their respective exchangeable pool, though homoscedasticity between the compared pools was not met for Mg. Our results are consistent with previous studies for Ca and K. Blum and Smith 41 showed, in an isotopic dilution assay using the 45 Ca radiogenic isotope over 16 different type of soils, that E Ca was significantly greater than Exch Ca for 6 soil samples, lower for 2 samples and not significantly different for 8 samples. Reeve et al 43 showed that 5 soil samples out of 7 showed an E Ca pool greater than the Exch Ca pool.…”
Section: Discussionsupporting
confidence: 93%
“…Using radio-isotopes, previous studies found that the K and Ca isotopically exchangeable pool was larger than the exchangeable pool (over 45 agricultural soil studied) [38][39][40][41][42][43] . Two recent studies 44,45 , focused on soil samples from the Breuil-Chenue experimental forest and using a stable isotopic dilution approach, (i) showed that soil pools of Mg, Ca and K in addition to the exchangeable pool significantly contributed to chemical equilibrium reactions between the liquid and solid phases of the soil, and (ii) suggested that these pools were supported by secondary non-crystalline mineral phases such as Al and Fe (hydr)oxides, and amorphous aluminosilicates.…”
mentioning
confidence: 99%
“…The weathering submodel in PROFILE was later built in to the dynamic version SAFE (Alveteg et al, 1995), which was mainly used for acidification assessments, but has also been used for studying the dynamics of weathering rates . Later, the SAFE model was coupled with the tree growth model PnET (Aber and Federer, 1992), the decomposition model DECOMP (Walse et al, 1998;Wallman et al, 2004) and the hydrological model PULSE (Lindström and , resulting in the forest ecosystem model ForSAFE (Wallman et al, 2005;Belyazid et al, 2006). The ForSAFE model simulates the integrated biogeochemical processes of a forest ecosystem.…”
Section: Modelling Based On Weathering Kineticsmentioning
confidence: 99%
“…There are several different pools of base cations in soil and also several different flows, e.g. decomposition, uptake, ion exchange and weathering, and it is difficult to distinguish between these different sources and sinks (Rosenstock et al, 2019) and to define the pools accurately (van der Heijden et al, 2018). Therefore, a number of indirect methods to quantify weathering rates have been developed: process-based modelling (Sverdrup and Warfvinge, 1993); soil measurements where the depletion of weathering products in different soil layers is determined in order to assess average weathering rates since soil formation (Olsson et al, 1993); and budget calculations where the flows in the mass balance, except weathering, are measured (Lundström, 1990;Jacks and Åberg, 1987;Wickman and Jacks, 1991;Sverdrup et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation